The method for determination the complex probabilistic effectiveness index of the State Border Guard Service of Ukraine operational activity - Басараб, О. К. (Problems of Informatization and Control, 2013)
In this article the method for determining the complex probabilistic effectiveness index of the StateBorder Guard Service of Ukraine operational activity was formed on the basis of simulation of telecommunicationnetworks, using mathematical apparatus of fuzzy numbers.